Avaliação numérica e experimental de absorvedores dinâmicos de vibrações ativos e adaptativos - Cunha Júnior, Sebastião Simões da (2004)
The use of Dynamic Vibration Absorbers (DVAs) has been seen as an interesting alternative to tackle the problem of vibration control, from the standpoints of efficiency and cost-effectiveness. In their simplest configuration, these devices are named passive DVAs, been formed by lumped single degree-of-freedom systems comprising inertia, damping and stiffness parameters. However, it is widely recognized that the practical utililty of passive DVAs is limited by the fact that they can only be designed to operate in a rather narrow, previously fixed, frequency band outside which their effectiveness cannot be ensured. To avoid such difficulty, it has been investigated novel configurations of DVAs which very frequently incorporate recent technological achievements. In this sense, this work addresses the use of two different alternatives to the classical passive DVAs, namely: the active DVAs, which contain an actuator fed with a control signal calculated from the vibration responses according to an adequate control law, and the so-called adaptive DVAs, understood as those whose parameters of inertia and/or damping and/or stiffness can be varied in a controlled, continuous way, by some kind of externai action. In both cases, it becomes possible to keep the absorbing device tuned to the excitation frequency, thus effective in a larger frequency band. In this work three configurations of active DVAs are assessed in terms of the underlying theory, numerical simulations and experimental appraisal, namely: a) an active DVA employing a feedback law expressed as a linear combination of the displacement, velocity and acceleration signals of the DVA mass with respect to the primary system; b) an active DVA based on the theory of classical optimal control; c) an active DVA using a modified optimal control strategy, which incorporates the excitation into the model and uses Artificial Neural Networks to enable automatic frequency tracking. It is also proposed a novel configuration of an electromechanical DVA, in which a passive DVA is combined with a RLC Circuit in such a way that frequency tuning can be achieved by changing the parameters of the electric Circuit. A particular interest in this configuration is the possibility of real time tuning by combining automatic frequency tracking with digital control of the parameters of the electric Circuit.